A solid-state 11B NMR and computational study of boron electric field gradient and chemical shift tensors in boronic acids and boronic esters - Weiss, Joseph W.E.; Bryce, David L. (Université d'Ottawa | University of Ottawa, 2010)
The results of a solid-state 11B NMR study of a series of 10 boronic acids and boronic esters with aromatic substituents are reported. Boron-11 electric field gradient (EFG) and chemical shift (CS) tensors obtained from analyses of spectra acquired in magnetic fields of 9.4 and 21.1 T are demonstrated to be useful for gaining insight into the molecular and electronic structure about the boron nucleus. Data collected at 21.1 T clearly show the effects of chemical shift anisotropy (CSA), with tensor spans (Ω) on the order of 10−40 ppm. Signal enhancements of up to 2.95 were achieved with a DFS-modified QCPMG pulse sequence. To understand the relationship between the measured tensors and the local structure better, calculations of the 11B EFG and magnetic shielding tensors for these compounds were conducted. The best agreement was found between experimental results and those obtained from GGA revPBE DFT calculations. A positive correlation was found between Ω and the dihedral angle (CCBO), which describes the orientation of the boronic acid/ester functional group relative to an aromatic system bound to boron. The small boron CSA is discussed in terms of paramagnetic shielding contributions as well as diamagnetic shielding contributions. Although there is a region of overlap, both Ω and the 11B quadrupolar coupling constants tend to be larger for boronic acids than for the esters. We conclude that the span is generally the most characteristic boron NMR parameter of the molecular and electronic environment for boronic acids and esters, and show that the values result from a delicate interplay of several competing factors, including hydrogen bonding, the value of CCBO, and the electron-donating or withdrawing substituents bound to the aromatic ring.